Pengaruh Penggunaan Teknologi Informasi, Efektivitas Sistem Informasi Akuntansi, Dan Sistem Pengendalian Intern Terhadap Kinerja Karyawan - Mirnasari, Putu Diah; Suardhika, I Made Sadha (E-Jurnal Akuntansi, 2018)
This study aims to determine the influence of the use of information technology, the effectiveness of accounting information systems, and internal control system on employee performance. This research was conducted at the Rural Bank in Denpasar City. In this research use saturated sampling technique. Respondents in this study as many as 75 employees who use computers in doing their work. The data in this research is obtained through observation, interview and questionnaire. Analytical techniques used are multiple linear regression analysis techniques and t test previously conducted testing of research instruments such as validity test, reliability and classical assumption test. Based on the result of research, it is known that the variable of information technology usage (X1), effectiveness of accounting information system (X2), and internal control system (X3) as a whole have positive effect on employee performance (Y). This study is expected to provide insight into the use of information technology, the effectiveness of accounting information systems and internal control systems on employee performance and will contribute positively to all parties, especially for the company. Keywords: Information technology, effectiveness of information system, internal control, employee performance.